Forgiveness no guilt, no grudges - Larsen, Sandy; Larsen, Dale; DeVelasco, Joe (Wheaton, IL Harold Shaw, 1984)
Study guide
13 inductive studies for students in junior and senior high.
Keywords: Forgiveness -- religious aspects -- Christianity -- study and teaching